DEVELOPING LOW-COST MANNEQUIN FOR UNDERGRADUATE IV LINE PHLEBOTOMY - Doni Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Skills laboratory training had been providing students the opportunity to practice medical skills in a longitudinal education curriculum with various methods. The integration of skills lab learning methods and the use of mannequins could provide the students to practice invasive medical procedures on patients like the real condition in the clinical setting, but still remains a safe simulation. However, simulations in the skills lab require commercial mannequins that have been imported with limited design options and very expensive prices. The effect of this expensive training will hamper institutions to facilitate students’ learning. Therefore, Clinical Skills Laboratory, Faculty of Medicine, Universetas Gadjah Mada had initiated to produce low-cost and innovative mannequins. This study is aimed to develop low-cost mannequin in order to facilitate learning.Methods: This study is a comparison study to 3 types of simple infusions mannequin which will be attached to simulated patients. These 3 types of mannequin are based from the materials: silicone, silicone plus oil, and latex. There were three groups of respondents: 30 students, 15 teachers, and 15 simulated patients and were randomly invited to review those mannequins using a questionnaire and structured interviews. The data were analyzed using Mann-Whitney test and an “inductive content analysis”.Results: The low-cost mannequins were highly accepted by the respondents and the best mannequin was made from silicone (p<0.05). However, the mannequins need improvement on the skin design and the prevention of fluid leakage from the pumps and tubes. These mannequins were designed to stimulate undergraduate students not only to practice inserting needle to veins, but also learning how to communicate with patients at the same time.Conclusion: These low-cost mannequins can be used to practice integrated clinical skills in skills laboratory education. However, the mannequins should be evaluated and improved regularly.